2020
DOI: 10.1186/s12883-020-01897-9
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the post-stroke immune response and cognitive functioning: the StrokeCog study protocol

Abstract: Background: Stroke increases the risk of cognitive impairment even several years after the stroke event. The exact mechanisms of post-stroke cognitive decline are unclear, but the immunological response to stroke might play a role. The aims of the StrokeCog study are to examine the associations between immunological responses and longterm post-stroke cognitive trajectories in individuals with ischemic stroke. Methods: StrokeCog is a single-center, prospective, observational, cohort study. Starting 6-12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In line with our protocol, DISCOVERY 24 also includes MRI and blood-based protein biomarkers, whereas STROKE-Cog has a focus on circulating blood biomarkers of immunological responses. 23 R4VaD 26 is mainly focused on dementia after stroke and includes blood biomarkers, whereas OX-CHRONIC 22 includes neuroimaging, but not biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our protocol, DISCOVERY 24 also includes MRI and blood-based protein biomarkers, whereas STROKE-Cog has a focus on circulating blood biomarkers of immunological responses. 23 R4VaD 26 is mainly focused on dementia after stroke and includes blood biomarkers, whereas OX-CHRONIC 22 includes neuroimaging, but not biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…We have in line with the previously mentioned R4VaD 26 study decided to include participants with aphasia and encourage them to complete the study protocol, if possible, while other ongoing studies have decided to exclude patients with aphasia. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The StrokeCog study is a longitudinal cohort study aiming to investigate the post-stroke immune response and cognitive functioning over the course of stroke recovery (29). Participants included in the parent study had ischemic strokes that were confirmed by MRI or CT scan, were over the age of 25, were able to return for annual follow-up visits, and had fluency in English.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Buckwalter shared the design of an ongoing clinical study at Stanford Hospital which is aimed at linking immunological responses to stroke with longterm post-stroke cognitive trajectories. 12 Samples are collected from patients and participants longitudinally, and immune profiling of peripheral blood mononuclear cells and plasma proteomics are used for analysis. Preliminary data indicate that numerous proteins associated with immunomodulation are significantly altered in the plasma of enrolled patients confirmed to have had an acute ischemic stroke.…”
mentioning
confidence: 99%
“…Buckwalter's group is actively investigating peripheral immune signatures after stroke that may be associated with future cognitive deterioration. Buckwalter shared the design of an ongoing clinical study at Stanford Hospital which is aimed at linking immunological responses to stroke with long‐term post‐stroke cognitive trajectories 12 . Samples are collected from patients and participants longitudinally, and immune profiling of peripheral blood mononuclear cells and plasma proteomics are used for analysis.…”
mentioning
confidence: 99%